2015
DOI: 10.2134/jeq2014.12.0527
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of the Agricultural Policy/Environmental eXtender (APEX) for Phosphorus Loads in Tile-Drained Landscapes

Abstract: Numerical modeling is an economical and feasible approach for quantifying the effects of best management practices on dissolved reactive phosphorus (DRP) loadings from agricultural fields. However, tools that simulate both surface and subsurface DRP pathways are limited and have not been robustly evaluated in tile-drained landscapes. The objectives of this study were to test the ability of the Agricultural Policy/Environmental eXtender (APEX), a widely used field-scale model, to simulate surface and tile P loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Rapid vertical transit of water to tile drains can occur during both saturated and unsaturated field conditions. One possible macropore pathway is associated with rapid vertical flux through earthworm burrows, root channels, and inter‐aggregate voids when saturation exceeds the “water‐entry” pressure of micropores, herein referred to as matrix‐excess macropore (MEM) flow (Jarvis, 2007; Deurer et al, 2009; Beven and Germann, 2013). Macropore flow has also been observed to occur at low antecedent moisture conditions as a result of desiccation crack networks that create direct conduits to subsurface pathways and the groundwater table, herein referred to as matrix‐desiccation macropore (MDM) flow (Bouma et al, 1978; Kneale and White, 1984; Shipitalo and Gibbs, 2000; Nimmo, 2012; Mirus and Nimmo, 2013).…”
mentioning
confidence: 99%
“…Rapid vertical transit of water to tile drains can occur during both saturated and unsaturated field conditions. One possible macropore pathway is associated with rapid vertical flux through earthworm burrows, root channels, and inter‐aggregate voids when saturation exceeds the “water‐entry” pressure of micropores, herein referred to as matrix‐excess macropore (MEM) flow (Jarvis, 2007; Deurer et al, 2009; Beven and Germann, 2013). Macropore flow has also been observed to occur at low antecedent moisture conditions as a result of desiccation crack networks that create direct conduits to subsurface pathways and the groundwater table, herein referred to as matrix‐desiccation macropore (MDM) flow (Bouma et al, 1978; Kneale and White, 1984; Shipitalo and Gibbs, 2000; Nimmo, 2012; Mirus and Nimmo, 2013).…”
mentioning
confidence: 99%
“…Numerical models, such as the NTT, are often criticized because many of them do not adequately capture P losses in subsurface pathways (Radcliffe et al, 2015), which is an important concern for states like Ohio where leaching can pose a large risk for P loss. A recent study, using a subset of the field dataset reported herein, showed that the Agricultural Policy/Environmental eXtenter (APEX) model, which is utilized as part of the NTT, was able to accurately simulate surface and subsurface P loading at annual timescales (Ford et al, 2015). Given the performance of the current Ohio PI and numerical models to predict a field's risk of P loss in tile‐drained landscapes, future research efforts should focus on using field datasets to calibrate and validate multiple‐site assessment tools to determine an accurate and preferred P management tool for Ohio so that consistent and reliable recommendations are made.…”
Section: Discussionmentioning
confidence: 99%
“…The APEX can also be used to assess the impact of land management practices, conservation practices, and global climate change. Furthermore, the APEX has the ability to assess the sustainability of agricultural system on a whole farm for a long term (1-4000 years) [17,20].…”
Section: Apex Model Descriptionmentioning
confidence: 99%